COVID-19 Vaccination Willingness Among People Living With HIV in Wuhan, China - Wu, Songjie; Ming, Fangzhao; Xing, Zhongyuan; Zhang, Zhiyue; Zhu, Shanhui; Guo, Wei; Zou, Shi; Liu, Jinli; Liu, Yang; Liang, Ke (Frontiers in Public Health, 2022)
Vaccination is essential to controlling the pandemic of coronavirus disease 2019 (COVID-19). People living with HIV (PLWH) were considered more vulnerable to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection compared with the general population. Therefore, it is urgent to protect PLWH from SARS-CoV-2 infection. For PLWH, vaccine hesitancy could be more common and may compromise vaccine coverage. Our study aimed to investigate the willingness to receive the COVID-19 vaccination among PLWH and associated factors. A cross-sectional online survey was performed among PLWH and the general population from 4 April to 18 April 2021 in Wuhan, China. The multivariable logistic regression was used to analyze associated factors for COVID-19 vaccination willingness among PLWH. A total of 556 PLWH and 570 individuals from the general population were enrolled. The COVID-19 vaccine willingness among PLWH was 60.8%, which was relatively lower than that in the general population (80.9%) (P < 0.001). The results of multivariable analysis indicated that PLWH with comorbidities (OR = 2.07, 95% CI: 1.25–3.45), those who had idea about PLWH would be more serious if they were infected with SARS-CoV-2 (OR = 1.67, 95% CI: 1.11–2.51) and those who thought their antiretroviral therapy (ART) would be affected by COVID-19 epidemic (OR = 2.04, 95% CI: 1.22–3.42) had higher willingness to receive COVID-19 vaccination. PLWH who had a monthly income over 5,000 RMB (OR = 0.64, 95% CI: 0.45–0.92) and had a sex orientation as non-homosexual (OR = 0.67, 95% CI: 0.47–0.96) were associated with lower willingness for COVID-19 vaccination. Our findings showed that the PLWH had a lower willingness for COVID-19 vaccination compared with the general population in Wuhan. Targeted interventions such as health education should be conducted to increase the willingness for COVID-19 vaccination among PLWH, thus enhancing COVID-19 vaccine uptake among PLWH.